International expansion of Ukrainian business into the EU market: analysis of the external environment and development prospects - Tymokhova, H.; Kovalov, Y.; Nesterenko, V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The paper presents a comprehensive analysis of the international expansion of Ukrainian businesses into the European Union market. In particular, the study is focused on identifying the main external barriers, competitive advantages, and development prospects of Ukrainian enterprises in the context of the rapidly changing global economic environment. The article examines in detail the EU’s regulatory requirements, cultural characteristics, and logistical challenges, which constitute significant obstacles for Ukrainian companies seeking to enter international markets. Within this research, practical case studies were showcased to illustrate the successful integration of Ukrainian companies into the European market. For instance, the experiences of Nova Poshta, Ajax Systems, and Farmak have been analyzed, demonstrating that by optimizing logistics chains, adapting products to meet the demands of European consumers, and implementing state-of-the-art technologies, considerable progress has been achieved even under severe geopolitical pressures. Moreover, the article evaluates the role of state support provided through cooperation with international organizations such as USAID, GIZ, and the EBRD, as well as the utilization of business platforms like Diia.Business. The paper outlines the methodological approaches adopted, which are based on the analysis of data from official sources (the Ministry of Economy, the National Bank of Ukraine) and recent scholarly publications. This integration of data has facilitated the development of a holistic picture of the external environment and the strategic measures required for enhancing the competitiveness of Ukrainian companies in the EU market. Special attention is given to assessing the impact of regulatory, cultural, and logistical factors and identifying effective market entry models. As a result, the paper formulates practical recommendations for enterprises aiming to expand beyond the domestic market to secure long-term stability and growth. Overall, the findings of the study provide a solid basis for a more systematic approach to international expansion, which is essential for establishing sustainable partnerships in a highly competitive global arena. The conclusions drawn from the article underscore the potential of the Ukrainian business sector to optimize production processes and adapt to the demands of foreign markets, thereby playing a key role in the country’s stable economic development.